ANALYSIS OF NITRATE, PHOSPHATE AND SILICATE CONTENT AND THEIR EFFECTS ON PLANKTONIC ABUNDANCE IN THE ESTUARY WATERS OF BATANG ARAU OR PADANG CITY WEST SUMATRA PROVINCE - Wahyuni, Weni; Amin, Bintal; Siregar, Sofyan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
The entry of nutrients (nitrate, phosphate and silicate) from land-based anthropogenic activities (industry, agriculture and household waste) through rivers can potentially cause changes in water quality and will affect fertility and aquatic organisms such as phytoplankton. These three nutrients play an important role in the living tissue cells of living organisms and in the photosynthesis process. This study aims to analyze the effect of nitrate, phosphate and silicate content on the plankton abundance in the estuary of the Batang Arau River, Padang, West Sumatra. The method used is a survey method, the determination of the sampling station is done by purposive sampling, data were analysed by Excel and SPSS Software. Based on the results of laboratory analysis, the nitrate content ranged from 0,117 to 0,485 mg/l, phosphate content from 0,239 to 0,704 mg/l, and silicate content from 0,031 to 0,685 mg/l. Planktonic diatom abundance in the estuary of the Batang Arau River ranges from 194 to 750 ind/l. The results of the statistical analysis of the effect of nitrate, phosphate and silicate with an abundance of diatoms are expressed by the equation Y = 743,019 - 481,828Nitrate - 199,552Phosphate - 172,971Silicate. This equation explains that the effect of nitrate, phosphate and silicate content on diatom abundance has an inverse or negative relationship, where nitrate, phosphate and silicate levels increase, the diatom abundance will decrease. The difference of content and the relationship between parameters analyzed in this research are discussed.